La forme financiarisée de la relation de crédit des collectivités locales. De la crise à l’institutionnalisation - Edoardo Ferlazzo (Revue de la Régulation)
The thesis focuses on the evolutions of local authorities’ credit relationship and studies the various forms it has taken over time. It develops an institutionnalist approach in which credit relationship, and its historical transformations, are captured from the regulations that frame, more or less loosely, the credit demand from local authorities on the one hand, and the credit supply of financial actors on the other. More particularly, and over the recent period, the thesis highlights the emergence and the institutionnalization of what I identify as a “financialized form”, characterized by the use of financial products, made available by financial markets, in local authorities’ debt management.